Consider the picture attached.
From right triangle trigonometry:
tan(α)=(opposite side)/(adjacent side)=15/67=0.2239
using a scientific calculator we find that arctan(0.2239)=12.62°
thus α=12.62°, is the angle that the vector makes with the positive x-axis.
The angle made with the + y-axis is 12.62°+90°=102.62°.
The length of the vector v can be determined using the Pythagorean theorem:
Thus, to make v a unit vector, without changing its direction, we need to divide v by |v|=68.8.
This means that the x and y components will also be divided by 68.8, by proportionality.
So, the unit vector in the direction of v is:
<span>(67/68.8)i + (-15/68.8)j=0.97 i + (- 0.22)j
</span>
Answer: 12.62°; 102.62°; 0.97 i + (- 0.22)j
Answer:
x° = 11°
<em>Z </em><em>FGI </em><em>=</em><em> </em><em> </em><em>6</em><em>0</em><em>°</em>
Step-by-step explanation:
<em>I</em><em>f</em><em> </em><em>GH</em><em> </em><em>bisects</em><em> </em><em>Z </em><em>FGI</em>
<em>then</em><em> </em><em>Z </em><em>FGH </em><em>=</em><em> </em><em>Z </em><em>H</em><em>GI</em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>or,</em><em> </em><em>(</em><em>3</em><em>x</em><em> </em><em>-</em><em> </em><em>3</em><em>)</em><em>°</em><em> </em><em>=</em><em> </em><em>(</em><em>4</em><em>x</em><em> </em><em>-</em><em> </em><em>1</em><em>4</em><em>)</em><em>°</em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>or,</em><em> </em><em>3</em><em>x</em><em>°</em><em> </em><em>-</em><em> </em><em> </em><em>4</em><em>x</em><em>°</em><em> </em><em>=</em><em> </em><em>-</em><em> </em><em>1</em><em>4</em><em>°</em><em> </em><em>+</em><em> </em><em>3</em><em>°</em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>or,</em><em> </em><em>x°</em><em> </em><em>=</em><em> </em><em>1</em><em>1</em><em>°</em>
<em>Z </em><em>FGI </em><em>=</em><em> </em><em>3</em><em>3</em><em>°</em><em> </em><em>-</em><em> </em><em>3</em><em>°</em><em> </em><em>+</em><em> </em><em>4</em><em>4</em><em>°</em><em> </em><em>-</em><em> </em><em>1</em><em>4</em><em>°</em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>=</em><em> </em><em> </em><em>6</em><em>0</em><em>°</em>
I think that the answer is quadratic
Answer: it will take 6 months for both gyms to cost the same.
Step-by-step explanation:
Let m represent the number of months that it will take for the cost of both gyms be the same.
At one gym, there is a $12 start-up fee, and after that each month, m, at the gym costs $20. This means that the total cost for m months is
12 + 20m
At another gym, each month at the gym costs $22. This means that the total cost for m months is 22m
For both costs to be the same, the number of months would be
12 + 20m = 22m
22m - 20m = 12
2m = 12
m = 12/2 = 6